Assessing the environmental and socio-economic impacts of artisanal chrome mining in Kamusha, ward 14, Mvurwi, Zimbabwe (2021-2024) - Dzumbunu, Ropafadzo Kimberly (BUSE, 2025)
This study examines the environmental and socio-economic impacts of artisanal chrome mining in Kamusha, Ward 14, Mvurwi, Zimbabwe, between 2021 and 2024. Artisanal and small-scale mining (ASM) has emerged as a critical livelihood strategy for many rural communities in Zimbabwe, yet it presents significant environmental and regulatory challenges. A mixed-methods approach was adopted, combining Geographic Information System (GIS)-based land use and land cover (LULC) change detection with qualitative data from focus group discussions (FGDs) and semi-structured interviews (SSIs). GIS analysis of Sentinel-2 satellite imagery revealed substantial land degradation, with a marked increase in bare land and loss of vegetated areas over the four years. Qualitative findings from local community members, artisanal miners, agricultural landowners, and government officials revealed widespread concerns about declining agricultural productivity, water contamination, deforestation, poor health outcomes, and weak policy enforcement. The study found that although Zimbabwe’s Mines and Minerals Act and Environmental Management Act provide regulatory frameworks for mining, enforcement remains limited. Local governance structures feel disempowered, and community coping mechanisms are under-supported. The study concludes that sustainable management of artisanal chrome mining requires improved monitoring, inclusive policy implementation, formalisation support, and stronger institutional coordination. The findings contribute to current debates on sustainable mining, environmental justice, and rural development in Zimbabwe and across sub-Saharan Africa.
Keywords: Artisanal and Small-Scale Mining (ASM); Chrome Mining; Environmental Impacts; Socio-Economic Impacts; Land Use and Land Cover (LULC); Geographic Information Systems (GIS); Land Degradation; Deforestation; Water Pollution; Rural Livelihoods; Agricultural Productivity